Screening and functional studies of long noncoding RNA in subjects with prediabetes - Zhang, Pan; Zhu, Xuan; Du, Yangguang; Dong, Zongmei; Qiao, Cheng; Li, Ting; Chen, Peipei; Lou, Peian (Endocrine, 2020)
Background In recent years, long noncoding RNAs (LncRNAs) have been found to play an important role in type 2 diabetes mellitus. However, research on the relationship between LncRNAs and prediabetes is still emerging. Objectives The study aim was to screen differently expressed LncRNAs and understand their localization and function in patients with prediabetes. Methods We used microarray analysis to screen LncRNAs in prediabetes participants.To further clarify the localization and function of the expressed mRNAs, we used gene ontology analysis and pathway analysis. Then, internal validations were performed using individual quantitative real-time polymerase chain reaction (qRT-PCR) assays. Results We identified 55 differently expressed LncRNAs and 36 mRNAs in prediabetes participants comparing with controls. Gene ontology analysis indicated that the most enriched transcript terms were multicellular organismal process, plasma membrane, and binding. Pathway analysis indicated that the differently expressed mRNAs were involved in processes such as starch and sucrose metabolism, pantothenate and coenzyme A biosynthesis, and nicotinate and nicotinamide metabolism. The qRT-PCR results showed a trend consistent with the microarray results in 30 patients and 30 healthy controls. Conclusions We found aberrantly expressed LncRNAs and mRNAs in prediabetes subjects, and demonstrated that these LncRNAs are involved in the entire prediabetes biological process.